Farm households' preference for cash-based compensation versus livelihood-enhancing programs: A choice experiment to inform avian flu compensation policy in Nigeria - Oparinde, Adewale; Birol, Ekin (International Food Policy Research Institute, 2011)
In this paper we attempt to bridge the resilience school of thought and incentive compatibility in livestock disease control policies through a pilot choice experiment study conducted on 104 farm households in the Nasarawa state of Nigeria. The aim of this study was to shed light on farm households' valuation of various compensation plan attributes and trade-offs among these attributes. In the experiment presented here, compensation plan was defined broadly to include not just the traditional attributes, such as the number of days it takes to receive the payment, the compensation rate, and the method of payment, but also more diverse interventions, such as training in biosecurity measures and access to bank loans, which are expected to have longer-term impacts on households' livelihood outcomes. We analyzed the data using various discrete choice models, the best-fitting of which was the random parameter (or mixed) logit model with interactions, which enabled us to capture both unobserved and observed heterogeneity in farm households' preferences for the compensation plan attributes. The results reveal that overall, study households preferred compensation plans that made payment in fewer days, provided facilitated credit access, and offered biosecurity training. Households with better-educated heads and those with lower income levels valued compensation plans that provided credit access and biosecurity training the most. These findings are expected to inform the design of efficient, effective, equitable, and targeted compensation policies, which could not only reduce the livestock disease risk but also improve the resilience of poor farm households' livelihoods against future poultry-related or other idiosyncratic shocks.